Emulsifier of Arthrobacter RAG-1: Chemical and Physical Properties - Zuckerberg, A. (1979)
The extracellular emulsifier of Arthrobacter RAG-1 was deproteinized by hot phenol treatment and purified by fractional precipitation with (NH(4))(2)SO(4). The active fraction, precipitating between 30 and 35% saturation [EF-RAG(UET) WA], appeared to be homogeneous by immunodiffusion and sedimentation analysis. EF-RAG(UET) WA had an intrinsic viscosity of 750 cm(3)/g, a sedimentation constant of 6.06S, a diffusion constant of 5.25 × 10(−8) cm(2) s(−1), and a partial molar volume of 0.712 cm(3) g(−1). From these data a weight average molecular weight of 9.76 × 10(5) and a viscosity average molecular weight of 9.88 × 10(5) were calculated. EF-RAG(UET)WA contained 46.7% C, 7.01% H, and 6.06% N. Titration of the nonreducing polymer gave a single inflection point (pK′ = 3.05), corresponding to 1.5 μmol of carboxyl groups per mg. Direct estimation of O-ester and hexose content of the highly acidic polymer yielded 0.65 and 0.29 μmol/mg, respectively. Mild alkaline hydrolysis released fatty acids with an average molecular weight of about 231. Strong acid hydrolysis of EF-RAG(UET)WA yielded d-glucose (minor), d-galactosamine (major), and an unidentified amino uronic acid (major).